2006
DOI: 10.18553/jmcp.2006.12.3.239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Blood Pressure Control to Adherence With Antihypertensive Monotherapy in 13 Managed Care Organizations

Abstract: ardiovascular disease, the leading cause of death and disability in the United States, is associated with inadequate blood pressure (BP) control.1,2 The relationship between BP and risk of cardiovascular events is positive, continuous, consistent, and independent of other risk factors. 2 Unfortunately, BP control is particularly poor among hypertensive patients at the highest risk for cardiovascular events, including patients with diabetes and older patients with systolic hypertension (HTN). 3Randomized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(246 citation statements)
references
References 36 publications
11
224
1
9
Order By: Relevance
“…Many studies demonstrated improved outcomes associated with better adherence to antihypertensives,5, 36 and nonadherence has been associated with increased risk for CVD, hospitalizations, and healthcare costs 5, 13, 14, 15, 16, 17, 37, 38, 39, 40, 41. In our study, around 60% of beneficiaries had PDC ≥80%, which is consistent with previous studies 9, 19.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies demonstrated improved outcomes associated with better adherence to antihypertensives,5, 36 and nonadherence has been associated with increased risk for CVD, hospitalizations, and healthcare costs 5, 13, 14, 15, 16, 17, 37, 38, 39, 40, 41. In our study, around 60% of beneficiaries had PDC ≥80%, which is consistent with previous studies 9, 19.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies suggest that chronic disease patients need to achieve 80 percent adherence to derive benefits from their medications. [14][15][16] We then defined a loss of adherence as being adherent in 2006 but being nonadherent in 2007. Similarly, we defined an increase in adherence as being nonadherent in 2006 and adherent in 2007.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Group-based trajectory models were used to identify and characterize patient subgroups following differential trajectories of adherence over time. 34,35 We first transformed the monthly PDC with oral hypoglycemics using the arcsine transformation, and modeled the monthly PDC using a censored normal distribution; the time variable was months since initiating treatment (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The purpose of the data transformation was to meet the assumption for the finite mixture trajectory model with a censored normal distribution for each trajectory.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…4 Adherence is routinely measured based on prescription refills using administrative claims data. These claims-based measures are used in health plan quality ratings, in identifying non-adherent patients for targeted interventions by health systems, in research investigating the impact of medication non-adherence on clinical outcomes 3,[5][6][7][8][9] and in predicting health care costs and utilization. [10][11][12] However, most studies, and all current quality reporting measures, use a single adherence measure to represent average medication refills in a year (e.g., proportion of days covered [PDC] above a predefined threshold).…”
Section: Introductionmentioning
confidence: 99%